DESIGN OF ISLAMIC HISTORY DOCUMENTARY IN THE SULTANCY BANTEN - Hirfat, Mohammad Alma; Sumarlin, Rully; Fiandra, Yosa (Telkom University, 2023)
Indonesia is the largest muslim country in the world with a muslim population of 236.53 million people or about 86.88% of the population. This is inseparable from the long history of the entry of Islam in the territory of Indonesia which was once known as the Nusantara region. The spread of Islam pioneered by traders in the midst of Hindu-Buddhist influence was very successful. Then came the various sultanates patterned Islam which helped in the spread of Islam throughout the archipelago one of which is the Sultanate of Banten. With the influence of the ruler, Islam can have a strong influence in the Land of Banten. But unfortunately the history seems to be lost and forgotten because the interest of young people to study history is very minimal. Therefore, the author is interested in designing a documentary entitled=History of Islam in the Sultanate of Banten